Kinerja Mesin Motor 4 Langkah dengan Bahan Bakar Campuran Bioetanol dan Pertamax - Indra Hermawan; Muhammad Idris; Darianto Darianto; M. Yusuf R Siahaan (Universitas Medan Area, 2021)
The availability of fossil fuels as an energy source is increasingly limited, so there is a need for new energy sources as environmentally friendly alternatives, one of which is bioethanol. Bioethanol is a type of biofuel sourced from living matter, usually plants with the chemical formula C2H5OH and the empirical formula C2H5O with an octane number of 108. One of the benefits of bioethanol for fuel mixtures is due to the higher octane value, flammability, heat of vaporization and higher oxygen content lowers cylinder temperature thereby reducing NOx emissions and producing less CO2. This study aims to evaluate the performance of a 4 stroke engine by comparing the use of Pertamax and bioethanol mixtures of fuel with a composition of 25%, 20%, and O% bioethanol. The study used an experimental method where data was collected and then data processing and data analysis were carried out. The results obtained the highest power of 8.70 kW at 25% bioethanol at 6000 rpm, followed by 20% bioethanol and 100% Pertamax at 8.60 rpm with rotations of 6500 rpm and 7000 rpm respectively. The highest torque of 25% bioethanol is 13.80 Nm at 5500 rpm, followed by 3.10 Nm at 5000 rpm at 100% pertamax and 12.80 Nm at 5500 rpm with 20% bioethanol fuel. The lowest fuel consumption is 0.57 kg/kWh at 7000 rpm with 100% pertamax fuel, then 0.60 kg/kWh with 20% bioethanol fuel at 6500 rpm and 0.6 kg/kWh with 15% bioethanol fuel at 6000 rpm